Captain marvel (2019), volume 9, part 1 ebook Revenge of the brood. - Thompson, Kelly (Captain Marvel (2019), 2023)
Collects CAPTAIN MARVEL (2019) #42-46. A nightmare mission to the stars changes everything for Captain Marvel! A mysterious degraded message from Rogue arrives at the same time that Carol's emergency beacon begins screaming with cries from Binary, and that cannot possibly be a coincidence. Captain Marvel assembles a team of allies - including Polaris, Gambit, Wolverine and Psylocke. But their rescue mission is soon derailed by a dangerous old enemy out for blood! The Brood has always been one of the most fearsome alien races in the galaxy. Now - under the rule of an Empress gone rogue, with a hive mind bent on revenge - will even Captain Marvel and the X-Men be enough to stop them?! Plus: As a mighty war rages that threatens the fate of the world, Captain Marvel - and her whole household - face Judgment Day!